The Impact of Global Commodity Prices and Macroeconomic Factors on ASEAN-6 Stock Markets: Panel Evidence (2019-2025) - Maskur Cahyanto; Eni Setyowati (Program Pascasarjana STIE Amkop Makassar, 2026)
This study analyzes the impact of global commodity prices and macroeconomic factors on stock market returns in ASEAN countries Indonesia, Malaysia, Thailand, Philippine, Singapore, and Vietnam. Duringthe periode from the first quarter of 2019 to the fourth quarter of 2025. The data used consist of quarterly secondary data sourced from the IMF for exchange rates, gold prices, oil prices, and inflation, and from investing.com for stock return data. The stock return, gold prices, oil prices, and exchange rate variables were transformed using log-return to improve data stasionarity. Using a panel data regression approach with 168 observations, model selection via Chow test, Lagrange Multiplier Test, and Hausman Test consistenly yielded the Common Effect Model (CEM) as the best estimation model.The estimation result show that gold price returns and exchange rate returns have a negative and significant effect at the 5% level, while inflation has a negative and significant effect at the 10% LEVEL. Conversely, oil price returns do not have a significant effect, indicating structural heterogeneity among countries in responding to energy price shocks. The exchange rate is the most dominant variable, confirming thaht exchange rate stability is a crucial factor for the performance of the ASEAN capital market. These findingshave important implications for the investors and policymakers in managing cross-country portofolio risk in the ASEAN region.